2019
DOI: 10.1186/s12887-019-1781-3
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial profile and antibacterial susceptibility of otitis media among pediatric patients in Hawassa, Southern Ethiopia: cross-sectional study

Abstract: BackgroundOtitis Media (OM) is the most common disease of childhood. Twenty thousand people die each year from otitis media. It is an important cause of preventable hearing loss, affects children's intellectual performance and language development. There are very small numbers of studies done in Ethiopia concerning this topic. This study aimed to identify bacterial pathogens related to ear infection and to assess antibacterial susceptibility of isolated organisms.MethodA cross-sectional study was conducted on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 13 publications
5
16
3
2
Order By: Relevance
“…ASOM was a more common diagnosis (68%) compared to CSOM (32%) among the study participants, an observation supported by other OM reports. 1 , 6 , 19 , 25 , 34 Moreover, the majority of the OM cases (74%) was observed among children under 5 years of age, similar to what have been reported in Ghana (65.1%) 10 and elsewhere (71.7%-84.2%) 3 , 8 , 35 for childhood OM. This observation could either be due to the immaturity of their immune system, which predisposes them to frequent upper respiratory tract infections, their relatively shorter Eustachian tube that allows for easier entry of nasopharyngeal pathogens into the middle ear, or both.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…ASOM was a more common diagnosis (68%) compared to CSOM (32%) among the study participants, an observation supported by other OM reports. 1 , 6 , 19 , 25 , 34 Moreover, the majority of the OM cases (74%) was observed among children under 5 years of age, similar to what have been reported in Ghana (65.1%) 10 and elsewhere (71.7%-84.2%) 3 , 8 , 35 for childhood OM. This observation could either be due to the immaturity of their immune system, which predisposes them to frequent upper respiratory tract infections, their relatively shorter Eustachian tube that allows for easier entry of nasopharyngeal pathogens into the middle ear, or both.…”
Section: Discussionsupporting
confidence: 84%
“…This observation could either be due to the immaturity of their immune system, which predisposes them to frequent upper respiratory tract infections, their relatively shorter Eustachian tube that allows for easier entry of nasopharyngeal pathogens into the middle ear, or both. 6 , 36 Similarly, a greater proportion of males (59%) was affected, which is comparable to the proportions of OM cases attributed to males in several studies (51.3%-62.3%), 8 , 34 , 35 , 37 albeit in contrast with others (48%-48.5%). 3 , 38…”
Section: Discussionsupporting
confidence: 76%
“…Our study is correlated with Gopichand WR et al, 11 and Tadesse et al, 14 in which most isolates are pure culture rather than the mixed one. In our study, the most common isolate was Pseudomonas species, and it was similar to other studies, where also Pseudomonas species predominantly found in 48-98% of patients 15,16,17 .…”
Section: Resultssupporting
confidence: 89%
“…This result is consistent with results reported in Ethiopia, including 80.4% in Bahir-Dar (2013–2015, 38) and 75.6% in Hawassa (a cross-sectional study). 28 However, it was lower than reported from other parts of Ethiopia, such as Gondar (2009–2012) (89.5%), 29 Dessie (2001–2011) (83.6%), 39 and Mikelle (98.2%). 27 Our result was slightly higher than reported from Bangladesh (70.8%).…”
Section: Discussionmentioning
confidence: 68%
“…However, there was a lower degree of resistance rate in Fluoroquinolones (23.33%), Aminoglycosides (23.73%), and Cephalosporins (29.78%). Studies from different parts of Ethiopia 28 , 38 , 39 , 47 , 48 also reported that most of the ear-discharge isolates were resistant to drugs in the Penicillin, Tetracycline, and Macrolide class. However, they reported that drugs in the Fluoroquinolones, Aminoglycosides, and Cephalosporins were better in treating ear-discharge bacterial isolates.…”
Section: Discussionmentioning
confidence: 98%